Impact of Soil and Water Conservation Measures and Slope Position on Selected Soil Attributes at a Watershed Scale - Melaku Alene Retta; Hailu Kendie Addis; Tesfaye Feyisa Beyene (Applied and Environmental Soil Science)
The Ethiopian highlands are affected by soil erosion resulting in the deterioration of soil properties. To reverse this, different soil and water conservation (SWC) measures were spatially practiced; however, the effect of SWC and slope gradient on soil properties is not well studied in the area. Hence, this study was conducted to evaluate the effects of SWC and slope gradient on selected soil physicochemical properties in Dawnt watershed, northwestern Ethiopia. The treatments were a combination of four different SWC measures on three slope gradients replicated at three sites. Disturbed and undisturbed soil samples were collected from 0–20 cm soil depth, and physicochemical properties were determined following standard laboratory procedures. The laboratory results depict that sand, bulk density, moisture, particle density, porosity, pH, organic carbon (OC), cation exchange capacity (CEC), total nitrogen, and available phosphorus were significantly (P<0.05) affected by SWC measures and slope gradient. High OC (2.44%), CEC (45 cmol (+) kg−1), and moisture (19.55%) were obtained from stone-faced soil bund stabilized with grass (SFSBG) and higher available phosphorus (7.83 ppm) from soil bund (SB), while lower bulk density (1.13 gm/cm3) was obtained from SFSBG. Additionally, higher clay (41.67%) and moisture (19.81%), and lower bulk density (1.14 g·cm−3) were obtained from the lower slope. Higher pH (6.75) and OC (2.89%) were recorded at the lower slope under SFSBG and lower pH and OC (6.03 and 1.02%) at the upper slope with nonconserved. Soil chemical properties, except available potassium, were increased down the slope. The interactions of slope position and SWC measures affect soil texture, pH, organic carbon, and available phosphorus but not affect soil bulk density, moisture content, particle density, total porosity, cation exchange capacity, total nitrogen, and available potassium. In general, the soil properties were improved through integrating conservation practices with multipurpose grass species across the study watershed. Therefore, it is possible to infer that SFSBG measures improve the observed physicochemical soil properties, which urge for the maintenance and the development of SWC measures in the study watershed as well as nearby highlands with similar topographic conditions and agroclimatic characteristics.